THE ARABIC ORIGINS OF ENGLISH AND EUROPEAN "PLACE NAMES": A CONSONANTAL RADICAL THEORY APPROACH - Jassem, Zaidan Ali (English Review: Journal of English Education, 2018)
This paper examines the Arabic origins of some common place names in English, German, French, Latin, Greek, Russian, and Sanskrit from a consonantal radical or lexical root theory perspective. The data consists of the names of around 60 key cities like Birmingham, Brighton, Cambridge, Chester, Derby, Essex, Exeter, Glasgow, London, Manchester, Oxford, Queensville, York, etc. The results clearly show that all such names have true Arabic cognates, with the same or similar forms and meanings whose different forms, however, are all found to be due to natural and plausible causes and different courses of linguistic change. Furthermore, they show that place names play an important role in both near and distant genetic relationships. As a consequence, the results indicate, contrary to Comparative Method and Family-Tree Model claims (e.g. Campbell 2013; Harper 2012-18), that Arabic, English, and all Indo-European languages belong to the same language, let alone the same family. Therefore, they prove the adequacy of the consonantal radical theory in relating English, German, French, Latin, and Greek to Arabic as their origin all because, unlike any other language in the group, it shares cognates with all of them in addition to its huge linguistic repertoire phonetically, phonologically, morphologically, syntactically, and semantically.Keywords: Place names, Arabic, English, German, French, Russian, Latin, Greek, Sanskrit, historical linguistics, consonantal radical/lexical root theory